The Microbial Community of a Passive Biochemical Reactor Treating Arsenic, Zinc, and Sulfate-Rich Seepage - Baldwin, Susan Anne; Khoshnoodi, Maryam; Rezadehbashi, Maryam; Taupp, Marcus; Hallam, Steven; Mattes, Al; Sanei, Hamed (Frontiers in Bioengineering and Biotechnology, 2015)
Sulfidogenic biochemical reactors for metal removal that use complex organic carbon have been shown to be effective in laboratory studies, but their performance in the field is highly variable. Successful operation depends on the types of microorganisms supported by the organic matrix, and factors affecting the community composition are unknown. A molecular survey of a field-based biochemical reactor that had been removing zinc and arsenic for over six years revealed that the microbial community was dominated by methanogens related to Methanocorpusculum sp. and Methanosarcina sp., which co-occurred with Bacteroidetes environmental groups, such as Vadin HA17, in places where the organic matter was more degraded. The metabolic potential for organic matter decomposition by Ruminococcaceae was prevalent in samples with more pyrolysable carbon. Rhodobium- and Hyphomicrobium-related genera within the Rhizobiales Order that have the metabolic potential for dark hydrogen fermentation and methylotrophy, and unclassified Comamonadaceae were the dominant Proteobacteria. The unclassified environmental group Sh765B-TzT-29 was an important Delta-Proteobacteria group in this BCR, that co-occurred with the dominant Rhizobiales OTUs. Organic matter degradation is one driver for shifting the microbial community composition and therefore possibly the performance of these bioreactors over time.